2007
DOI: 10.2224/sbp.2007.35.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Illness Transmission Mode and Perceiver Personality: Factors Affecting Stigmatized Perceptions of Patients and Sexual Illness

Abstract: Past field research has demonstrated the devastating impact of illness stigma on patient populations; experimental studies have identified specific illness characteristics that influence stigmatization and social rejection of patients. The current study used a quasi-experimental design to investigate the influence of participant erotophobia-erotophilia (Fisher, Byrne, & White, 1983) and illness transmission (nonsexual, sexual) on perceptions of illness and patients. Sexual illness transmission led to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Of those 53%, fear of stigma accounted for 26% of the reasoning for not seeking treatment. Smith and Nave (2007) indicated social rejection scores of erotophobes towards fictitious patients with sexually transmitted infections were higher in their study than those of fictitious patients with non-sexually transmitted illnesses.…”
Section: Erotophobia and Erotophiliamentioning
confidence: 61%
See 1 more Smart Citation
“…Of those 53%, fear of stigma accounted for 26% of the reasoning for not seeking treatment. Smith and Nave (2007) indicated social rejection scores of erotophobes towards fictitious patients with sexually transmitted infections were higher in their study than those of fictitious patients with non-sexually transmitted illnesses.…”
Section: Erotophobia and Erotophiliamentioning
confidence: 61%
“…These stigmas not only contribute to social rejection, but have also been shown to contribute to depression, anxiety, and stress among people suffering from sexually related illness (Smith & Nave, 2007;Fife & Wright, 2000;Barth, et al, 2002;Crandall & Moriarty, 1995) and sexual dysfunction.…”
Section: Erotophobia and Erotophiliamentioning
confidence: 99%
“…In contrast, erotophobic individuals are more likely to stigmatize individuals with sexually transmitted infections (Smith & Nave, 2007), and they demonstrate lower levels of sexual knowledge and are less likely to seek out sex education (Fisher et al, 1988; Gerrard, Kurylo, & Reis, 1991). In addition, some have found that erotophobic individuals voluntarily look at sexual stimuli for shorter durations than erotophilic individuals (Becker & Byrne, 1985), suggesting that erotophobia and erotophilia translate into biases relevant to the processing of sexual stimuli, possibly even outside of an individual's conscious awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Research comparing perceptions of individuals with illnesses that differ only on transmission mode (sexual or nonsexual) has shown that individuals with an STI are more likely to be rejected and viewed as immoral; that is, they are more likely to be stigmatized (Smith et al., ; Smith & Nave, ; Young et al., ). Although this tells us that sexual transmission of illnesses is stigmatizing, there is much less research on factors contributing to this stigmatization.…”
mentioning
confidence: 99%